EFEKTIFITAS PEMANFAATAN GETAH BUNGA KAMBOJA UNTUK MENGHILANGKAN SAKIT GIGI DI MASA PANDEMI COVID-19 - I Made Budi Artawa; Ni Made Sirat; Ni Nyoman Dewi Supariani (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
Toothache is an acute pain condition that requires immediate treatment. One of the herbal ingredients to treat toothache is frangipani flower sap because it is believed to contain anti-pain compounds such as alkaloids, tannins, flavonoids and tritepenoids which also function as antibiotics. Scientific evidence regarding the safety and effectiveness of using frangipani flower sap must be known so that the author is interested in writing "Is frangipani flower sap effective for overcoming tooth pain during the covid-19 pandemic?" The purpose of this study was to determine the effectiveness of frangipani flower sap on tooth pain during the covid-19 pandemic. Research method with literature study. By reviewing various previous research results that already exist, both from books and journals that are relevant to the problem, then they are discussed and conclusions are made. This research was conducted in 2021. Results and discussion, Sriwarthini NLPN et al., 2017 research results found that all concentrations of frangipani sap ethyl acetate extract ranging from 5, 20, 35, 50 and 65% were effective in inhibiting the growth of pathogenic fungi and forming an inhibition zone included in very strong category. The results of the research by Sukarjati, 2013 showed that the concentration of frangipani sap extract had a significant effect (P0.05) on the growth of S. aureus. The highest power of frangipani sap extract on the growth of S. aureus was obtained at a concentration of 25%. The results of Heyne's research, 1987 The frangipani sap is useful as a pain reliever due to cavities, treats swollen gums and can ripen ulcers. The results of the research by Sulistyarsi, 2012 showed that there were differences in the inhibition zone of frangipani leaf extract against S. aureus p value = 0.01 0.05. In the inhibition test, better results were obtained against Staphylococcus aureus bacteria with the lowest concentration of 25% and the inhibition zone of 23.66 mm. Sirisha, 2014 frangipani sap extract has analgesic and antibacterial and antifungal effects. The frangipani extract contains alkaloids, flavonoids, saponins, steroids, tannins, glycosides and carbohydrates. Flavonoids and tannins dictate the role of pain inhibitors. This mechanism is driven by its effect as a prostaglandin inhibitor. The presence of active compounds in frangipani sap can reduce nociceptor activity on the tooth surface so that it can temporarily reduce pain. The conclusion is that frangipani flower sap is a safe, inexpensive and effective alternative to toothache treatment for treating acute toothache without complications in patients during the COVID-19 pandemic era.